Evaluasi Kinerja dan Pengukuran Hasil dalam Administrasi Publik: Pendekatan dan Metode Terbaru - Purwanti, Tri; Suharti, Sri; Unsardi, Firman; Deprianata, Rendika (SENGKUNI Journal (Social Science and Humanities Studies), 2022)
Performance evaluation and outcome measurement are crucial aspects of public administration that play an important role in assessing the effectiveness, efficiency, and impact of government policies and programs. In a continuous effort to improve public services and meet public expectations, new approaches and methods have been introduced. This article will review some innovative approaches to performance evaluation and outcome measurement in public administration, and how these approaches can help governments make better decisions and improve public.